Rare Mineral Evidence of Mahsuri Ring Meteorite Impact in Langkawi Island - Catur Cahyaningsih; Husnul Kausarian; Yogi Aditia (Journal of Applied Geospatial Information, 2019)
The research area was conducted in Ulu Melaka Village, district of Langkawi, Kedah Province, Malaysia. Coordinate of research area around latitude 99°45'97" to 99°45'04" N and longitude 06°25'05" to 06°20'00"E, with coverage area around 7 x 5 km. This research area is a suspected meteorite impact crater. The analysis begins by taking 7 rock sediment samples spread around the research area. The aim of research to find evidence of meteorite impact has fallen around research area use geochemistry method refer to the content of Rare Minerals of rock samples in the study area. Rock samples were processed using an X-ray diffraction (XRD) machine and run by EVA Software. Rock samples which have been analyzed were S1, S2, S3, S4, S5, S10, S19. Result of the analysis found four types of minerals formed by a meteorite impact consist of Jagoite, Dickite, Rubidium and Germanium Silicate Zinc Sulfide Diaminopropane. Jagoite and Dickite found in sample S2, Rubidium Germanium Silicate in sample S4 and Zinc Sulfide Diaminopropane in samples S10 and S19, respectively .